Legal Framework of Medical Service in the City of Osijek During the First Half of the 19th Century - Čandrlić, Slavko (Medicine, Law & Society, 2024)
The aim of this research work is to gain insight into how the medical service was legally regulated in the city of Osijek, the main Slavonian center to which a large number of people immigrated after the Great Turkish War, and which consequently spread the fear of the appearance of new infections in that area. At the same time, special attention was paid to medical regulations after the city of Osijek received the status of a Free Royal City in 1809. Despite the jurisdiction of the Royal Hungarian – Protectoral Council and the Royal Hungarian Court Chamber, the Liberation Charter enabled the city of Osijek to establish its own self-governing bodies. Thus, along with the City Council and its representatives, a lesser- known physical department was founded, which was headed by a physicist. In particular, it was a physician with the highest level of responsibility, who had the authority to protect the public health of the population of the Free Royal City of Osijek.